Nation or District? Evaluating the Territorial Scope of Bills through Experimental Designs - Simison, Emilia (2017)
This paper studies the territorial scope of the bills presented by members of the Chamber of Deputies (the lower chamber of the Argentine National Congress) during Juan Domingo Perón?s first two terms in office (1946?1955). Its main objective is to observe the effect that modifying the electoral system (switching from incomplete party ballots in multimember districts to relative majorities in single-member districts) had on that scope. Experimental techniques (an interrupted time-series and a within-subjects design) are used to analyze a novel database including every bill presented in the Chamber of Deputies during the period in question. Contrary to theoretical expectations, an increase is observed in the share of bills with a territorial scope that goes beyond deputies? districts ? especially for those presented by legislators from the opposition and from larger provinces. In addition, by separately analyzing the effect on the ruling party and the opposition, the paper uncovers a plausible explanation for previous nonconclusive findings.